2016
DOI: 10.1016/j.supflu.2015.10.020
|View full text |Cite
|
Sign up to set email alerts
|

Stability of materials in supercritical ammonia solutions

Abstract: Improvements to the growth of nitride crystals in ammonothermal growth environments can be achieved through improved autoclave designs, purity, and use of in-situ monitoring techniques. Given the limited data available on the stability of materials in supercritical ammonia solutions, this study intends to broaden the known dataset by experimentally investigating the mechanical and chemical stability of 35 bulk metals, 2 bulk metalloids, and 17 bulk ceramics while identifying suitable materials for future in-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
43
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(43 citation statements)
references
References 46 publications
0
43
0
Order By: Relevance
“…Typically employed materials in different research groups include Inconel 625, Inconel 718,R enØ 41, as well as Haynes 282 alloy. [16,[155][156][157] Exemplarily,a utoclaves with uppert emperature limits of 900 Ka t3 00 MPa or 1100 Ka t 150-170MPa were constructed, dependento nt he respective materials pecifications and the autoclave design ( Figure 11).…”
Section: Autoclaves and Liner Conceptsmentioning
confidence: 99%
See 1 more Smart Citation
“…Typically employed materials in different research groups include Inconel 625, Inconel 718,R enØ 41, as well as Haynes 282 alloy. [16,[155][156][157] Exemplarily,a utoclaves with uppert emperature limits of 900 Ka t3 00 MPa or 1100 Ka t 150-170MPa were constructed, dependento nt he respective materials pecifications and the autoclave design ( Figure 11).…”
Section: Autoclaves and Liner Conceptsmentioning
confidence: 99%
“…[158,159] Liners or capsules are used to prevent corrosion of the autoclaves and to avoid incorporation of transition metalsi nto the products.R ecently,n umerous materials were screened in terms of their chemicals tability, using pure NH 3 ,N aNH 2 ,o rN H 4 Cl. [155] Another study investigated the behavioro fN H 4 X( X= F, Cl, I) solutions on diverse metallic samples. [160] Severalm aterials were found to be applicable as liner materials, such as molybdenum for pure supercritical NH 3 , NaNH 2 ,N H 4 F, and NH 4 Cl solutions, as well as silver for supercritical NH 3 ,N aNH 2 ,a nd NH 4 Fs olutions.…”
Section: Autoclaves and Liner Conceptsmentioning
confidence: 99%
“…Cobalt alloys and molybdenum materials are potentially stable and robust materials. 10 This paper will explore the suitability of using pure molybdenum for a capsule system for creating a high purity, basic ammonothermal GaN growth environment. Silver was deliberately added to certain growth runs to determine any impact on growth.…”
Section: Introductionmentioning
confidence: 99%
“…Mineralizers can be basic (such as Na or K) which increase the concentration of NH 2 ions or acidic (such as NH 4 Cl or NH 4 I) which increase the concentration of NH 4 + ions. Acidic and basic ammonothermal environments cause different corrosion with autoclave components [6,7], so the mineralizer type must be considered when developing the autoclave.…”
Section: Introductionmentioning
confidence: 99%
“…[12,14] Recent work has indicated that molybdenum and its alloys may make suitable pressure bearing autoclave wall materials as they show little or no indication of corrosion in the ammonothermal environment with either fluoride or chloride chemistry. [7,17] An inert autoclave body would eliminate the need to integrate cumbersome and expensive liners, possibly reducing the cost for ammonothermal growth. Molybdenum and its alloys may be powder sintered to larger dimensions than ingot based nickel chromium super-alloy autoclaves which may open pathways to new industrial implementations for this growth method.…”
Section: Introductionmentioning
confidence: 99%